Upaya Kepala Sekolah dalam Mengembangkan Kompetensi Guru untuk Meningkatkan Mutu Pendidikan pada SMA Negeri di Kota Banda Aceh - Amiruddin Amiruddin (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2018)
Improving the quality of education is the responsibility of all stake holders, especially teachers during the process of learning in the classroom. Therefore, there is a need for teacher competence development that is influenced by various factors such as the principal's efforts. Based on this, the author wants to conduct a research entitled efforts of the principal school in developing teacher competence to improve the quality of education in the Public Senior High School in Banda Aceh which aims to determine the factors that can affect, the constraints faced and the efforts of principals in developing teachers’competency to improve the quality of education at SMA Negeri Kota Banda Aceh. Population and sample in this study were all principals of Public Senior High School in Banda Aceh as many as 16 headmaster are taken as sample (total sample). This is a descriptive research method with qualitative approach. data were collected through observation, interviews, and documentaries. Data was analyzed using simple statistics that is by tabulating the data in the table, calculating frequency and percentage then drawing conclusion. The results showed that the factors that affect teachers’ competence and the quality of education is the effort of the principal, training attended by teachers; learning facilities; teaching experience, health condition and educational background. Constraints faced against pedagogical and professional competence. The principal's efforts to develop highly effective and efficient teacher competencies can be done through MGMP empowerment, academic and clinical supervision and workshops or training with peers in schools. Students’ learning achievement can be increased by giving extra class in the afternoon, enrichment, remedial, and regular try out.